THE USE OF INFORMATION SYSTEMS IN THE BUSINESS ENVIRONMENT: focus on the benefits achieved - Martins, Jaqueline Castro; Campos, Ronaldo Ribeiro de (Revista Interface Tecnológica, 2021)
The present work presents a study focused on the use of information technology in the business environment with a focus on information systems, since many companies invest in this type of system to achieve better results. The work aims to present the benefits that the use of information technology, incorporated into the environments of information systems provide for companies. The methodologies used to carry out the study were based on Bibliographic research, carried out through books, websites and periodicals made available electronically, together with the technical application of data collection. Fifty (50) articles on information systems adopted in different areas of the organizations were selected. After an analysis to locate the described benefits, the results point to a coherence between the benefits indicated by the literature on the subject and those found in the implementations made by the organizations, highlighting the issues of a better information flow and decision-making process.